Gastric cancer: Decreasing incidence but stable survival in the Netherlands. (January 2014) - Dassen, Anneriet E.; Dikken, Johan L.; Bosscha, Koop; Wouters, Michel W. J. M.; Cats, Annemieke; van de Velde, Cornelis J. H.; Coebergh, Jan-Willem; Lemmens, Valery E. P. P.
Abstract: Background. Gastric cardia and non-cardia cancer exhibit differences in biological and epidemiological features across the world. The aims of this study were to analyze trends in incidence, stage distribution, and survival over a 20-year period in the Netherlands, separately for both types of gastric cancer. Methods. Data on all patients with a diagnosis of gastric cancer in the period 1989–2008 were obtained from the nationwide Netherlands Cancer Registry. Time trends in incidence [analyzed as European Standard Rate per 100 000 (ESR)] and relative survival were separately analyzed for cardia and non-cardia gastric cancer. Results. A total of 47 295 patients were included. Incidence rates per 100 000 for cardia cancer declined from 5.7 to 4.3 for males and remained stable for females (1.2). For non-cardia cancer, the incidence in males declined from 25 to 14 and in females from 10 to 7. Proportional incidence in stage IV cardia and non-cardia cancer increased in 2004–2008 (cardia 32–42%, non-cardia 33–45%). Five-year survival rates for stage I–III and X (unknown) remained stable (cardia cancer: 20%, non-cardia gastric cancer: 31%). Five-year survival for stage IV disease was 1.9% and 1.0% for cardia and non-cardia gastric cancer. Conclusion. The incidence of gastric cancer in the Netherlands markedly decreased over the past decades, in particular of non-cardia cancer. Survival remained dismal. Improvement of survival remains a challenge for the multidisciplinary team involved in gastric cancer treatment.